The politics of nationalism and ethnicity - Kellas, James G. (St. Martin's Press, 1998)
In this comprehensively revised and updated new edition, James Kellas reviews and assesses the main theoretical approaches to the study of nationalism that have been developed within a wide range of disciplines. He introduces a range of international case studies to explain the power of nationalism and ethnicity in politics, to identify the circumstances in which they flourish, and to evaluate various strategies of accommodation which have been developed to contain ethnic conflict.